Self-Assembled Molecules - New Kind of Protein Ligands Supramolecular Ligands - Roterman, Irena; Konieczny, Leszek (Springer Nature, 2017)
immunotargeting techniques; ligands; intramolecular immunological signals; congo red amyloids